2000
DOI: 10.1002/chin.200050118
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Porphyrins and Their Derivatives. Part 21. Unsymmetrical Dimeric Porphyrins (IV)

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…5 However, alcohol 5 (R ) 3,5-di-tert-butyl) was not among the products. These experiments confirmed that the Friedel-Crafts reaction occurred in high yield but also that the cyclization, similar to that of the β-formylporphyrins, [6][7][8][9] followed by an elimination, operated at an even faster rate when not inhibited.…”
supporting
confidence: 63%
“…5 However, alcohol 5 (R ) 3,5-di-tert-butyl) was not among the products. These experiments confirmed that the Friedel-Crafts reaction occurred in high yield but also that the cyclization, similar to that of the β-formylporphyrins, [6][7][8][9] followed by an elimination, operated at an even faster rate when not inhibited.…”
supporting
confidence: 63%
“…The usual route to ketone 1 requires first the formylation of a metalloporphyrin under Vilsmeier-Haack conditions followed by acid-catalyzed cyclization of the aldehyde and demetalation of the porphyrin. 13 The cyclization reaction was usually run under the oxidative conditions described by Ishkov and Zhilina, 14 to optimize the conversion to the ketone. Demetalation had to be done carefully to avoid a second cyclization previously described by Dolphin and co-workers for meso-tetraanisylporphyrins.…”
Section: Preparation Of Enaminoketonesmentioning
confidence: 99%
“…A first structure determination, albeit of low resolution, was published for the copper complex of ketone 1 in 1980. 13a During the course of this work, we determined the structure of chlorin 14 14 (Figure 1) and tosylhydrazine 13. In addition to specific features, the two structures have in common a six-membered ring fused to the porphyrin at a mesoand a β-position.…”
Section: Preparation Of Enaminoketonesmentioning
confidence: 99%
“…The reaction could be directed toward better yields of ketone 13 (+ a little 15) when run in the presence of chloranil [13]. Interestingly, under minor changes of the reaction conditions and when the complexing metal is copper, the isomeric ketone 15 (M = Cu), arising from the isomeric allylic alcohol, turned out to be the major product [14].…”
Section: Acid-catalyzed Cyclization Of 2-formylporphyrinsmentioning
confidence: 99%